A Comparative Study of the Anticoagulant and Antithrombotic Effects of Unfractionated Heparin and a Low Molecular Weight Heparin (Fraxiparine®) in an Experimental Model of Human Venous Thrombosis - Diquélou, Armelle; Dupouy, Dominique; Cariou, Roger; Sakariassen, Kjell S; Boneu, Bernard; Cadroy, Yves (Thrombosis and Haemostasis, 1995)
We have compared the anticoagulant and the antithrombotic effects of unfractionated heparin(Calciparine®)and low molecular weight heparin(Fraxiparine®)in an experimental human venous thrombosis model.One single subcutaneous injection of Calciparine® or Fraxiparine® was administered to healthy male volunteers at one month intervalin a randomised and cross-over design.Ten subjects received doses used in man for preventing venous thrombosis(5,000 IU and 3,075 IU,respectively),and seven other subjects received curative doses (12,500 IU and 6,150 IU, respectively).Thrombus formation was measured 3 h and 8 h after drug administration.Non-anticoagulated humanblood was drawn for 5 min directly from an antecubital vein over confluent cultured endothelial cells positioned in a parallel-plate perfusion chamber.The cells were previously stimulated for 4 h with lipopolysaccharides(10 µg/ml) and interleukin 1β(50 U/ml),resulting in optimal expression of biological active tissue factor.The wall shear rate at the cell surface was 50 s-1 and mimicked venous blood flow conditions.Immunologically quantified fibrin deposition on the stimulated cells was reduced only by curative doses of Calciparine® and Fraxiparine® at 3 h(3.4 ± 0.8 versus 1.0 ± 0.2 µg/cm2 and 2.6 ± 0.8 versus 1.0 ± 0.1 µg/cm2, respectively,p ≤0.05).The influence of Calciparine® and Fraxiparine® on the formation of thrombin and fibrin was determined by measuring the plasma levels of thrombin-antithrombin III complexes and fibrinopeptide A (FPA) in blood samples collected distally to the perfusion chamber.The generation of these markers was significantly inhibited (50-83%) by both prophylactic and curative doses of Calciparine® and Fraxiparine®(p ≤0.05).However, Fraxiparine® still significantly inhibited the thrombin and fibrin generation at 8 h (p ≤0.05), whereas Calciparine® did not.The antithrombotic effects of both heparins were correlated with their plasma activities as measured by the antifactor Xa or the antithrombin assays.Thus,it appears in this model that Calciparine® and Fraxiparine® produce comparable antithrombotic effects at clinically comparable doses. However Fraxiparine® has a longer-lasting anticoagulant activity than Calciparine®. These results are ingood agreement with clinical observations in man,and thus in favour of our model of human venous thrombogenesis for further studies of antithrombotic molecules.